Pengaruh Current Ratio dan Quick Ratio terhadap Return on Assets pada Sektor Healthcare yang Terdaftar di BEI Tahun 2021 – 2023 - Mayanti, Yuni; Barkah, Muhammad Caesario (Jurnal Maps (Manajemen Perbankan Syariah), 2025)
This study aims to obtain empirical evidence regarding the effect of the current ratio (CR) and quick ratio (QR) on return on assets (ROA) in the healthcare sector listed on the Indonesia Stock Exchange in 2021-2023. This study uses secondary data in the form of annual reports. The population used was 36 healthcare companies and the sample was determined at 11 companies using purposive sampling. The research method uses descriptive research with a quantitative approach. The data analysis technique uses multiple linear regression with the help of the SPSS program for Windows version 25. The results of this study explain that CR  and QR  partially affect ROA of healthcare companies listed on the Indonesia Stock Exchange and CR and QR  simultaneously have a significant effect on ROA healthcare.